Pengaruh Retaliasi Dan Power Distance Terhadap Niat Melakukan Whistleblowing - Malwa Conella; Sany Dwita (Universitas Negeri Padang, 2020)
This study aims to test empirically about: 1) The effect of retaliation on the intention to do whistleblowing, 2) the effect of power distance on the intention to do whistleblowing. This type of research is classified as a quasi experiment. The data in the study were collected by distributing questionnaires online using google form to 152 accounting student class 2016 and 2017 from a university in the city of Padang. Data analysis was performed using ANOVA. The results of this study conclude that retaliation does not affect an individual in whistleblowing intentions, and power distance can affect an individual in whistleblowing intentions. This study focuses on the importance of the threat of retaliation to new employees in companies / public sector organizations, as well as the culture of an organization. This study uses accounting students as experimental subjects to examine the effect of retaliation and power distance on the intention to do whistleblowing